2021
DOI: 10.1002/stem.3352
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C-β-dependent changes in the glucose metabolism of bone marrow stromal cells of chronic lymphocytic leukemia

Abstract: Survival of chronic lymphocytic leukemia (CLL) cells critically depends on the support of an adapted and therefore appropriate tumor microenvironment. Increasing evidence suggests that B-cell receptor-associated kinases such as protein kinase C-β (PKCβ) or Lyn kinase are essential for the formation of a microenvironment supporting leukemic growth. Here, we describe the impact of PKCβ on the glucose metabolism in bone marrow stromal cells (BMSC) upon CLL contact. BMSC get activated by CLL contact expressing str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…In CLL, protein kinases in the stroma such as PKCβ promote disease progression and influence therapy response 6 . Besides inducing metabolic changes, PKCβ activates NFκΒ and TFEB in stromal cells, thereby regulating proteins involved in CLL contact like VCAM1 30,55 . We similarly demonstrated that stromal LYN stimulated comparable inflammatory signaling pathways and sustained CLL survival in a contact-dependent manner, agreeing with previous studies that direct cell contact was required for the feeding of CLL cells 30,[56][57][58] .…”
Section: Discussionmentioning
confidence: 99%
“…In CLL, protein kinases in the stroma such as PKCβ promote disease progression and influence therapy response 6 . Besides inducing metabolic changes, PKCβ activates NFκΒ and TFEB in stromal cells, thereby regulating proteins involved in CLL contact like VCAM1 30,55 . We similarly demonstrated that stromal LYN stimulated comparable inflammatory signaling pathways and sustained CLL survival in a contact-dependent manner, agreeing with previous studies that direct cell contact was required for the feeding of CLL cells 30,[56][57][58] .…”
Section: Discussionmentioning
confidence: 99%
“…Concurrent administration of 2-deoxy-glucose and IACS-010759 suppressed this compensatory glycolysis and induced CLL cells apoptosis ( Vangapandu et al, 2018 ). Protein kinase C-β (PKCβ) also plays a critical role in the BM stroma and CLL cell interaction, where they provide a cancer-supportive inflammatory microenvironment ( vom Stein et al, 2023 ), chemoresistance ( Amigo-Jiménez et al, 2015 ), and establish metabolic symbiosis ( von Heydebrand et al, 2021 ). An interaction through PKCβ reduced glycolysis and insulin signaling in the BM-stromal cells and simultaneously increased the glycolysis/lactate production in CLL cells.…”
Section: Role Of Mscs and Their Adipocytic Lineage In Hematological M...mentioning
confidence: 99%
“…Corroborating this scenario, CLL cells isolated from blood samples are non-dividing, although their metabolism is still active [147]. In this context, Jitschin and colleagues reported that CLL cells acquire an increased glucose dependency upon contact with stromal cells [146], in turn promoting glucose uptake in CLL cells by decreasing mitochondrial stress and apoptosis [148]. However, this outcome is still debated.…”
Section: Role Of Mscs In In Chronic Lymphocytic Leukemiamentioning
confidence: 99%
“…Therefore, as also described, is possible that leukemic cells modify MSCs' metabolism to satisfy their energy demand. Recently, it was reported that after contact with CLL cells, MSCs switch their metabolism toward OXPHOS with consequent lower glucose usage, which might be an advantage for CLL survival [148].…”
Section: Role Of Mscs In In Chronic Lymphocytic Leukemiamentioning
confidence: 99%